Comparative Evaluation of Various Standard Methods in Leaching Test of Radioactive Waste Form - 김기홍; 유영걸; 정경기; 홍권표; 이락희; 김헌; 정의영; 고덕준; Ki-Hong Kim; Young-Gerl Ryu; Kyung-Ki Chung; Kwon-Pyo Hong; et al. (Journal of nuclear fuel cycle and waste technology (Online), 2003)
IAEA, FT-04-020 및 ANS 16.1의 침출시험법을 각각 수행하여 얻은 시험결과를 이용하여 상호 비교 평가하였다. 붕산을 함유한 파라핀 및 시멘트 고화체에서의 Co 과 Cs의 ANS 16.1의 침출지수는 6이상이었으나 고화매질과 탈염수의 종류에 따라 상반되는 침출거동을 보였다. 침출수로 합성해수와 탈염수를 사용하였을 경우 Co는 시멘트 고화체에서는 합성해수, 파라핀 고화체에서는 탈염수에서 침출이 높았다. 반면에 Cs의 침출정도는 시멘트에서는 탈염수, 파라핀에서는 합성해수에서 높았다. Co의 침출분율은 시멘트 고화체에서 IAEA ＞ ANS ＞ FT의 순으로 높았으며, 반대로 파라핀고화체에서는 이의 역순이었다. IAEA, FT-04-020, and ANS 16.1, standard leaching test methods, were evaluated comparatively with their test results. Leaching index of Co and Cs by ANS 16.1 method for waste forms of paraffin and cement were above 6.0. Their leaching behavior were depending on the type of matrix and leachant. Leachability of Co for cement waste form was higher in simulated seawater than do-mineralized water, and was higher in de-mineralized water for paraffin waste form. leachability of Co was contrary to Cs. Cumulative fraction leached of Co was higher in order or IAEA ＞ ANS ＞ FT in a cement waste form.